Image-Guided Percutaneous Splenic Biopsy and Drainage - Sammon, Jennifer; Twomey, Maria; Crush, Lee; Maher, Michael M.; O'Connor, Owen J. (Seminars in Interventional Radiology, 2012)
Percutaneous splenic biopsy and drainage are relatively safe and accurate procedures. The risk of major complication (1.3%) following percutaneous splenic biopsy does not exceed that of other solid intra-abdominal organ biopsies, and it has less morbidity and mortality than splenectomy. Both computed tomography and ultrasound can be used to provide image guidance for biopsy and drainage. The safety profile of fine-needle aspiration cytology is better than core needle biopsy, but core biopsy has superior diagnostic accuracy.
Keywords: spleen; biopsy; drainage; computed tomography; ultrasound; interventional radiology